Agrarian Conflict Resolution In The Construction Of Frans Seda Airport In Sikka Regency To Realize National Security - Andreas Gama Lusi; Arifudin Uksan; M. Adnan Madjid (CV. AFDIFAL MAJU BERKAH, 2024)
The development of Frans Seda Airport land addition as a strategic tourism and economic door is faced with a conflict. The problems that occur are caused by the transfer of community agrarian land that is converted by the government. The transfer of land ownership or land chosen by the community was not in line with the cost of land compensation that was provided, causing conflict escalation. The purpose of this research is to describe the conflict resolution of Frans Seda Airport Development in Sikka Regency to realize national security. The method used is a qualitative method with a descriptive approach through literature study. Based on the results of the research, it can be understood that the phenomenon of land conversion that occurs in Sikka Regency as a result of the airport development policy has several social impacts. The impacts are the shift of agrarian land into additional land for the airport, the loss of agricultural land as a source of livelihood for the surrounding community, the emergence of pro and contra attitudes in the community, and the emergence of social conflicts. The social conflicts are between the pro and con communities (horizontal conflict), and the contra communities, and the Sikka regional government (vertical conflict). Peace efforts were made by both government and non-government institutions. The Sikka Regional Government made persuasive efforts to mediate the conflicting parties. Litigation as a resolution is then initiated with dialogue, negotiation, and individual approaches, as well as maximizing compensation and community empowerment. Resolution orientation to conflict transformation is dominant in mediating conflicts. It is hoped that this research will contribute to encouraging functional groups to formulate a cross-sectoral, integrated, and coordinated agrarian conflict resolution mechanism for the development of public interests.